The Moderating Role of ESG Disclosure on The Relationship Between Growth Opportunities, Financial Constraints, and Investment Decisions - Tessa Vanina Soetanto; Adelina Proboyo; Lianto Lianto (Master of Management, School of Business and Management, Petra Christian University, 2025)
This study investigated the role of ESG disclosure in moderating the relationship between growth opportunities, financial constraints, and corporate investment decisions. While growth opportunities usually encourage firms to invest more, financial constraints often limit their capability to do so. ESG performance, reflecting a company’s commitment to sustainable and responsible practices, influences how firms navigate these two conflicting forces. 174 firm-year observations of publicly listed manufacturing companies in Indonesia from 2017–2023 were analyzed and processed using the Least Squares Dummy Variable (LSDV) estimator, clustered by year, in Stata 19. The results showed that ESG disclosure significantly moderated the relationship between financial constraints and investment decisions, but did not moderate the relationship between growth opportunities and investment decisions. The result suggests that manufacturing firms should adopt more ESG practices to improve access to financing and make better investment decisions.